EKSPERIMENTASI PENGAJARAN MATEMATIKA MELALUI PENDEKATAN SAVI TERHADAP PRESTASI BELAJAR SISWA DI MTs AL-HUDA PEKANBARU - -, Jufri (Edu Research, 2014)
The purpose of this study is to know the distinction of the students’ learning achievement between those who has been given conventional methods thepopulation ave all student of class V111 of MTs Alhuda pekanbaru. The sample is taken by using random sampling technique, which homogeneity has been tested then it is decided that the group of the experiment is 32 students of class V111.1 and the controlling students are 32 students of class V111.3 the methods in collecting the data are test and documentation. The analysis of the data uses test tand SPSS.